Effect of Titanium dioxide nanoparticles on the flexural strength of polymethylmethacrylate: An in vitro study - P Harini; Kasim Mohamed; T V Padmanabhan (Wolters Kluwer Medknow Publications, 2014)
Context: To improve the flexural strength of polymethylmethacrylate (PMMA). Aim: To evaluate whether the incorporation of titanium dioxide nanoparticles in polymethylmethacrylate (PMMA) increases the flexural strength and to compare the different concentrations of titanium dioxide nanoparticles and its relation to flexural strength. Settings and Design: Study was conducted in Sri Ramachandra University utilizing 40 specimens manufactured from clear heat polymerizing acrylic resin. Materials and Methods: Forty specimens of clear heat polymerizing acrylic resin of dimensions 65 Χ 10 Χ 3 mm as per ISO 1,567 standardization were fabricated and were grouped into A (CONTROL) with no titanium dioxide (TiO2) nanoparticles, B with 0.5 gms of TiO 2 nanoparticles, C with 1 gm of TiO 2 nanoparticles and D with 2.5 gms of TiO 2 nanoparticles added.The concentrations of titanium dioxide in each group were 1 wt%, 2 wt% and 5 wt%. Universal testing machine INSTRON was used to load at the center of the specimen with a cross head speed of 1.50 mm/min and a span length of 40.00 mm. Statistical Analysis Used: ANOVA and multiple comparisons are carried out using the independent t-test. Results: The ANOVA result shows that there is a significant difference between the groups with respect to the mean flexural strength. Highest mean flexural strength is observed in Group D, while the lowest is seen in Group A. Independent t-test revealed that there was a statistical significance between Group A and Group D (0.041) and between Group B and Group D (0.028). Conclusions: The results concluded that polymethylmethacrylate reinforced with different concentrations of titanium dioxide nanoparticles showed superior flexural strength than those of normal PMMA.